Rationality in Islamic Creed: Analyzing the Pillars of Faith in the Learning Islam Using Logic Podcast - Wulandari, Latifah; Rubino, Rubino (Yayasan Sembilan Pemuda Indonesia, 2025)
The transformation of Islamic preaching in the digital era has given birth to a rational, dialogical, and contextual religious approach. This research aims to explain the gap that Islamic faith is often seen as dogmatic, while this study examines its presentation rationally through digital media. The object of study is the podcast “Belajar Islam Pake Logika/Learning Islam Using Logic” on Raymond Chin’s YouTube channel featuring Ustadz Felix Siauw. The research uses descriptive qualitative methods with content analysis techniques. The primary data is in the form of a transcript of a 1 hour 28 minutes podcast, analyzed through thematic coding based on the six pillars of faith, with data validity reinforced through theory and source triangulation. The results of the study show that faith in Allah is the most dominant theme (10 out of 17 quotes), presented through logical arguments, awareness of monotheism, worship, and understanding life’s tests. Other pillars of faith, such as faith in the prophets, scriptures, the Day of Judgment, and destiny (qada and qadar), are also discussed rationally and practically. Meanwhile, faith in angels is not explicitly addressed, indicating limitations in the metaphysical aspect. The novelty of this research lies in the in-depth analysis of presenting the pillars of faith rationally in digital media, which has rarely been studied before. Its practical implication is that the rational approach to da’wah can serve as a bridge between reason and revelation, while also being relevant to meet the intellectual needs of critical generations in the information era. The contribution of this research is to provide perspectives for preachers, educators, and media managers in designing content that balances rationality with the completeness of doctrinal material.